(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article highlights the methodological aspects of using collaborative learning technologies in teaching the subject "History of Uzbekistan" to students. It analyzes the role of approaches based on teamwork, mutual communication, and active participation in increasing the effectiveness of the educational process. The study also scientifically demonstrates that collaborative teaching methods broaden students’ historical thinking, develop independent and critical thinking skills, and contribute to the deep acquisition of scientific knowledge. The article presents the advantages and methodological recommendations for teaching the History of Uzbekistan through modern pedagogical technologies, interactive methods, and group discussions.